The Effect of Cash Holding, Firm Size, and Financial Leverage to Earning Management in State-Owned Enterprises (SOEs) - Muhammad Elmas Fadlli; Khairunnisa M.M. (Journal of Accounting Auditing and Business, 2020)
This research was conducted to determine the simultaneous and partial influence between cash holding, firm size, and financial leverage on earnings management in SOEs Companies listed on the Indonesia Stock Exchange during 2012-2018. The method in this study used a quantitative method. This research uses descriptive research with case study research type. The sampling technique in this study used a purposive sampling technique by obtaining 12 sample companies with a period of 7 years to obtain 84 sample units. This research used a logistic regression analysis method using SPSS 25.0 software. The results of this study indicate that cash holding variables, firm size, and financial leverage simultaneously have a significant effect on earnings management. While partially, cash holding variables, firm size, and financial leverage do not affect earnings management.